Next generation models of carbonate mineral growth and dissolution. Issue 3 (22nd January 2014) - Stack, Andrew G.
Abstract The long‐term success of carbon sequestration lies in part on the ability to trap carbon dioxide as a carbonate mineral phase. As such, the ability to predict the extent of carbonate mineral precipitation over the lifetime of a proposed geologic sequestration site will be necessary. In this review, different methods of predicting the growth of carbonate minerals, particularly calcite, and their disadvantages and advantages are summarized. Starting from a simple description of the solution saturation state, more advanced affinity‐based models are described that comprise the status quo. In these, the reaction rate is measured by the difference in concentration from an equilibrium value or the Gibbs Free Energy of reaction. It is shown that these models fail to capture some important aspects of carbonate mineral growth rates. Next‐generation models in development are those that reflect the processes that occur on a mineral surface while it is growing, not just the concentration of dissolved species. While incomplete, these process‐based models are already addressing some long‐standing questions in geochemistry and are enhancing the accuracy and robustness of the predictive ability for calcite precipitation. Lastly, the importance of the step density, analogous to the reactive site density in a natural sample, is shown. The factors that may influence the step density are described and the potentially complex relationship between step density and solution conditions is presented. While still in development, these models suggest that many of the historical problems in quantitative prediction of mineral growth and dissolution reactions can be resolved.